2019
DOI: 10.1145/3269980
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Framework for Compression and Compressed Sensing of Light Fields and Light Field Videos

Abstract: Over the last decade we have seen the field of computational photography, especially light field and multi-view imaging, emerge and mature as a new paradigm in imaging technology. These technologies enable a range of novel applications ranging from advanced multidimensional image processing such as refocusing [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 82 publications
0
35
0
Order By: Relevance
“…It has been shown that data driven dictionary learning algorithms outperform analytical basis functions in terms of compression ratio and reconstruction quality [AEB06, MBPS09, MKU13, SPRE18, APF17]. Miandji et al [MHU19] presented a dictionary learning method for compression and compressed sensing of light field videos. The training procedure leads to an Aggregate Multidimensional Dictionary Ensemble (AMDE).…”
Section: Light Field Pipeline Design and Overviewmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown that data driven dictionary learning algorithms outperform analytical basis functions in terms of compression ratio and reconstruction quality [AEB06, MBPS09, MKU13, SPRE18, APF17]. Miandji et al [MHU19] presented a dictionary learning method for compression and compressed sensing of light field videos. The training procedure leads to an Aggregate Multidimensional Dictionary Ensemble (AMDE).…”
Section: Light Field Pipeline Design and Overviewmentioning
confidence: 99%
“…natural images). Finally, the size of AMDE is orders of magnitude smaller than overcomplete dictionaries such as Kā€SVD and its variants [MHU19]. Based on the above arguments, we use AMDE as the underlying representation for light field video data points.…”
Section: Light Field Pipeline Design and Overviewmentioning
confidence: 99%
See 3 more Smart Citations